Effect of feed dilution the with date kernels treated in different ways on some blood traits of broiler - Muhammad Jodi Shahid; Zahra’a Razzaq Hussain (University of Thi-Qar Journal of agricultural research, 2022)
This experiment was conducted at the poultry field, Agricultural Research and Experiments Station, College of Agriculture and the Marshes, Thi Qar University, from 11/1/2021 to 12/12/2021, to determine the effect of diluting the feed with date kernels treated in different ways on some productive traits of broilers. A total of 270, one day, 40 gm chicks of Rose-308 were used. Chicks were randomly distributed to the five experimental treatments with three replicates (18 birds for each replicate), the diets were provided from the beginning of the second week until the end of the sixth week. The treatments were as follows: T1: Standard control diet (without dilution); T2: control diet diluted by 20% regular date seed pods for 7-42 days; T3: basal diet diluted with 20% date kernels, cooked for 7-42 days; T4: basal diet diluted with 20% vinegar-treated seed for 7-42 days; T5: basal diet diluted by 20% seed germinated for 7-42 days. The results indicated a significant increase on the cellular blood characteristics (Red Blood Cell Count, White Blood Cell Count, Hemoglobin concentration and the Packed Cell volume) in all dilution treatments with date kernel powder, whether treated or untreated. A significant increase on the concentration of albumin, globulin and total protein with a significant decrease in the concentration of glucose, cholesterol and triglycerides in the dilution treatments with date kernel powder compared to the control treatment.